Modeling and Realization of Cavity-Backed Dual Band SIW Antenna - Belen, Mehmet A.; Mahouti, Peyman; Caliskan, Alper; Belen, Aysu (APPLIED COMPUTATIONAL ELECTROMAGNETICS SOC, 2017)
Herein, substrate integrated waveguide technology is applied in order to design high performance dual-band microstrip patch antennas. Two microstrip patch antenna designs were studied and modeled in 3D electromagnetic simulators. The obtained optimal models were then realized and measured. The measurement performance of the proposed antenna designs were then measured for 2.4 and 5.6 GHz. The results suggest that the proposed model consisting of a modified microstrip cavity-backed antenna and a defected ground structure is a high performance and low cost solution for 2.4 and 5.6 GHz applications.
Keywords: Antenna design; defected ground structure; dual band; cavity-backed antenna; Substrate integrated waveguide; Engineering; Telecommunications